2007
DOI: 10.4049/jimmunol.179.7.4424
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Transfer of Carcinoembryonic Antigen from Tumor Cells to NK Cells

Abstract: The inhibition of NK cell killing is mainly mediated via the interaction of NK inhibitory receptors with MHC class I proteins. In addition, we have previously demonstrated that NK cells are inhibited in a class I MHC-independent manner via homophilic carcinoembryonic Ag (CEA) cell adhesion molecules (CEACAM1)-CEACAM1 and heterophilic CEACAM1-CEA interactions. However, the cross-talk between immune effector cells and their target cells is not limited to cell interactions per se, but also involves a specific exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, the physiological response to IPT is likely to be dependent on the nature of transferred proteins as well as the cell type of the recipient cell. Recent studies have demonstrated a physiological role of IPT in other systems, including initiation and modulation of immune responses and supporting cell survival (Roda-Navarro et al 2006;McCann et al 2007;Stern-Ginossar et al 2007;Yasuda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the physiological response to IPT is likely to be dependent on the nature of transferred proteins as well as the cell type of the recipient cell. Recent studies have demonstrated a physiological role of IPT in other systems, including initiation and modulation of immune responses and supporting cell survival (Roda-Navarro et al 2006;McCann et al 2007;Stern-Ginossar et al 2007;Yasuda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While IPT was previously observed in several in vitro and ex vivo models (Rustom et al 2004;Rechavi et al 2007;Stern-Ginossar et al 2007;Davis and Sowinski 2008;Abounit and Zurzolo 2012), evidence of transfer in vivo in mammals is limited. We therefore aimed to monitor IPT in vivo.…”
Section: Ipt Occurs In Vivomentioning
confidence: 99%
“…Although Stern et al [6,19] reported that recombinant CEA and CEA transfected in mammalian cells inhibited the cytotoxicity of NK cells via CEACAM1, which is one of the receptors of CEA, in this study, we found that native soluble CEA in MPE did not play a role in the impairment of NK cell cytotoxicity. Native CEA is a highly glycosylated macromolecule, and this glycosylation plays a critical role in its function [20].…”
Section: Discussionmentioning
confidence: 41%
“…Lipophilic dyes (8, 15, 32, 33), biotin (15, 16, 23) and genetic engineering of the target cell to produce fluorescent peptide-MHC complexes were utilized to study trogocytosis (3436). As an alternative to these manipulations we propose to rely on the pool of antibodies against tumor antigens, which are familiar, available and easy-to-use for most immunologists.…”
Section: Discussionmentioning
confidence: 99%
“…Gary et al documented the transfer of melanoma cell surface antigen (MCSP/CSPG4) to CD8 T cells (11) and Stern-Ginossar et al showed the transfer of carcinoembrionic antigen (CEA) to NK cells interacting with tumor cells (36). Until now, the consequences of tumor antigen transfer have not been explored; the transformation of lymphocytes to secondary APC is currently under research in our laboratory.…”
Section: Discussionmentioning
confidence: 99%